MG-147 Canadian open genetics repository (COGR): A unified clinical genome database as a community resource for standardising and sharing genetic interpretations. (4th December 2015) - Wang, Marina; White, Shana; Lebo, Matthew S; Lerner-Ellis, Jordan
Abstract : Background: The utility of DNA variant databases created by Canadian laboratories is compromised by the many differences between them and data has become increasingly difficult to share. There is a critical need for collaborative measures between institutions to better facilitate variant analysis and information transfer. Objectives: The Canadian Open Genetics Repository (COGR) is a collaborative effort for the collection, sharing and analysis of variants reported by medical diagnostics laboratories across Canada. Using a commonly shared platform, a large repository will be constructed consisting of information related to human gene DNA variants and their relationship to disease. Design/method: COGR uses GeneInsight™, a database featuring full versioning of variant assessments and interpretations, security, and role-based editing of variant information. COGR provides each participating lab with an instance of the application as well as a Variant Assessment Tool. Results: The COGR network currently contains 3802 variants across 56 genes associated with 13 diseases. In total, 396 variants have been identified in more than one lab including 50 that have been identified by three labs. Around half of commonly identified variants have concordant classifications across labs. Conclusions: As an ongoing endeavour and a permanent resource, COGR will facilitate collaboration between Canadian laboratories and with the international efforts to develop tools and methods for taking full advantage of clinical laboratory data. We expect as more labs begin sharing data, this resource will lead to more consistent reporting, generation of knowledge rings and ultimately improve patient care.